2015
DOI: 10.3389/fonc.2014.00379
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Chaperones and Their Roles in the Immunogenicity of Cancer Vaccines

Abstract: The endoplasmic reticulum (ER) is a major site of passage for proteins en route to other organelles, to the cell surface, and to the extracellular space. It is also the transport route for peptides generated in the cytosol by the proteasome into the ER for loading onto major histocompatibility complex class I (MHC I) molecules for eventual antigen presentation at the cell surface. Chaperones within the ER are critical for many of these processes; however, outside the ER certain of those chaperones may play imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 173 publications
0
15
0
3
Order By: Relevance
“…Endoplasmic reticulum (ER) chaperones, including BiP/ GRP78, calreticulin, calnexin, GRP94, and ERP57, are a large family of proteins that have been discovered to have many important roles in maintaining ER homeostasis and contributing to cancer cell survival and progression. The correlation between ER chaperone expression and tumorigenesis has been extensively studied in various cancers, and most reports have indicated that these proteins promote the proliferation, migration, and attachment of cancer cells (9)(10)(11)(12)(13). The ER chaperone calnexin, which is an ER-specific type I transmembrane protein, regulates the folding and quality control of newly synthesized glycoproteins (14).…”
Section: Introductionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) chaperones, including BiP/ GRP78, calreticulin, calnexin, GRP94, and ERP57, are a large family of proteins that have been discovered to have many important roles in maintaining ER homeostasis and contributing to cancer cell survival and progression. The correlation between ER chaperone expression and tumorigenesis has been extensively studied in various cancers, and most reports have indicated that these proteins promote the proliferation, migration, and attachment of cancer cells (9)(10)(11)(12)(13). The ER chaperone calnexin, which is an ER-specific type I transmembrane protein, regulates the folding and quality control of newly synthesized glycoproteins (14).…”
Section: Introductionmentioning
confidence: 99%
“…Chaperony ER se mohou díky lokalizaci do buněčné membrány nebo extracelulárního prostředí přímo podílet na modulaci imunitní odpovědi buněk [29]. Imunogenní vlastnosti extracelulárních chaperonů ER jsou spjaté s proteiny, které se na povrchu buňky chovají jako "signál označující nebezpečí" a jsou schopné interagovat s receptory buněk imunitního systému.…”
Section: Imunogenní Vlastnosti Chaperonů Erunclassified
“…Kalnexin patří stejně jako kalretikulin mezi proteiny ER detekované na buněčné membráně. Funkcí povrlární chaperony, jako jsou HSP27, HSP60, HSP70, GRP94, HSP90 nebo GRP170, se mohou vázat s TLR (toll like receptor) receptory, které jsou obvykle exprimovány dendritickými buňkami a makrofágy, a tudíž se účastní vrozené imunitní odpovědi organizmu [29]. Jako chaperony ER schopné aktivovat imunitní systém na povrchu buňky nebo v extracelulár-ním prostředí byly popsány kalretikulin, GRP78 a GRP94 [30][31][32][33][34].…”
Section: Kalretikulin a Kalnexinunclassified
“…As an alternative to the stealth-like cancer eradication by TCR-transduced T cells, Graner and colleagues have proposed a more “blanket-bombing” approach. They describe the development of a vaccination rationale comprising of chaperone-rich cell lysates (CRCL) purified from solid tumors designed to induce a plethora of immune responses ( 30 ).…”
Section: War and Peacementioning
confidence: 99%